Core Needle Biopsy of Spinal Lesions under CT Guidance: Review of 79 Cases - Kaltsikis, Ioannis; Chourmouzi, Danai; Drevelegas, Kostas; Potsi, Stamatia; Moumtzouoglou, Anestis; Drevelegas, Antonios (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
The authors report the results of a retrospective study about computed tomography (CT)-guided percutaneous vertebral biopsies in 79 cases (44 males and 35 females, aged from 6 to 84 years old). Five biopsies were performed at the cervical level, 31 at the thoracic, 30 at the lumbar, and 13 at the sacrum. A diagnosis was obtained in 75 out of the 79 patients. Diagnostic yield was 95%, and diagnostic accuracy was 97.3%. Core needle biopsy under CT guidance for spinal lesions is a fast, relatively simple, minimally invasive, and low-cost method, with high levels of diagnostic accuracy and few complications. It plays a major role in the correct diagnosis and therapeutic planning. CT guidance allows safe and accurate biopsy of osseous lesions throughout the spine, obviating invasive open biopsy in most cases.
Keywords: spinal lesion; core needle biopsy; CT guidance